2005
DOI: 10.1016/j.worlddev.2004.09.022
|View full text |Cite
|
Sign up to set email alerts
|

Beyond comparative anecdotalism: lessons on civil society and participation from São Paulo, Brazil

Abstract: Summary. -Detailed fieldwork in São Paulo, Brazil, shows that the conventional understanding of civil society and citizen participation is flawed in two major ways. The dominant focus on the participation of individual citizens is misplaced, as it is civil organizations representing different sectors of the poor that participate in substantial numbers in participatory institutions. The civil society approach in international development suggests that the most effective voice of the poor in policy making comes … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
50
0
11

Year Published

2008
2008
2020
2020

Publication Types

Select...
7
3

Relationship

1
9

Authors

Journals

citations
Cited by 123 publications
(62 citation statements)
references
References 13 publications
1
50
0
11
Order By: Relevance
“…The respondents who participated in the field research in 2011 were selected using 'snowball' sampling (n=20) to find key 'gatekeepers' and gain access to other key players in this small island community (Gurza Lavalle et al, 2005) who were employed in tourism sectors and in different capacities. Others were approached using convenience sampling (n=4) as the researchers were going about their business on-island.…”
Section: (B) Methodologymentioning
confidence: 99%
“…The respondents who participated in the field research in 2011 were selected using 'snowball' sampling (n=20) to find key 'gatekeepers' and gain access to other key players in this small island community (Gurza Lavalle et al, 2005) who were employed in tourism sectors and in different capacities. Others were approached using convenience sampling (n=4) as the researchers were going about their business on-island.…”
Section: (B) Methodologymentioning
confidence: 99%
“…The absence of a strong domestic social democratic party in the country meant that radical NGOs also needed to distance themselves from national parties and electoral processes, but this also limited their ability to promote the political interests of their beneficiaries. Lavalle et al (2005) found that citizens in Brazil could only influence politics when they participated in civil society organizations and not as individuals. But they also found that these civil society organizations could only generate transformative actions when they were linked to political parties, rather than by remaining independent from them as much mainstream civil society theory assumes.…”
Section: Resource Flows: Donor Dependence and Changing Prioritiesmentioning
confidence: 99%
“…While post-colonial analyses question whether elite, professionalised NGO workers can genuinely understand and effectively channel the interests of low-income marginalised groups (Chatterjee, 2004), others highlight the political capital generated by their ability to move with fluidity between state, market and civil society spheres (Uvin and Miller, 1996;Lavalle et al, 2005). Middle-class professionals have also been found to be critical mediators within the cross-class alliances that have contributed to the effectiveness of demand-side initiatives (Jenkins, 2006).…”
Section: Ngos and Social Accountabilitymentioning
confidence: 99%